PENGARUH PROFESSIONAL FEE AUDIT, AUDIT DELAY TERHADAP KUALITAS AUDIT DENGAN KOMITE AUDIT SEBAGAI PEMODERASI (Studi Empiris pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2021) - Riska Damayanti (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Professional Fee Audit, Audit Delay on Audit Quality with the Audit Committee as a moderator of the LQ45 index companies listed on the Indonesia Stock Exchange in 2018-2021. The population in this study is the LQ45 index companies listed on the Indonesia Stock Exchange in 2018. 2018-2021, the sampling technique uses the purposive sampling method and produces 32 companies. Data analysis used logistic regression test using the Eviews 9 application. The results showed that Professional Audit Fee, Audit Delay had a simultaneous effect on Audit Quality. Against the partial test Professional Fee Audit has no effect on Audit Quality, Audit Delay has an effect on Audit Quality, the Audit Committee is not able to moderate the influence of Professional Audit Fee on Audit Quality while the Audit Committee is able to moderate the effect of Audit Delay on Audit Quality